Assessing Ergonomic Risks of Work-related Musculoskeletal Disorders in Soap Making Industries in Nigeria - Omotunde MUYIWA; Fatai Adeigbe; Adekunle Kolawole (The Indonesian Journal of Community and Occupational Medicine, 2025)
Introduction: Workers in manufacturing industry are frequently exposed to occupational dangers associated with work-related musculoskeletal disorders. However, few studies were available on work-related musculoskeletal disorders amidst workers in Nigeria’s soap making industry. Objective: To assesses ergonomic risk associated with work-related musculoskeletal disorders (WMSDs) in soap production. Method: Twenty purposively selected soap baking workers from four industries; work postures were assessed. Semi-structured oral questionnaires were used to appraise body areas where participants experienced the WMSDs. Workplace inspections were done by observing soap baking workers engaged in their various tasks. The semi-structured oral questionnaires and observation data collected were analysed using descriptive statistics and the Ovako Working Posture Analysis System. Result: The descriptive statistics revealed that the participants experienced pain/discomfort arising from their work, with the body parts most commonly affected been the lower back, wrists-hands, shoulders, and upper back (100%), respectively, elbows, and ankles/feet (75%), respectively, and neck (50%). Participants identified ergonomic risk were frequent twisting and bending during dragging of soap cake into the conveyor from cylinder cooler hopper as the prominent cause of the ache. Conclusion: The workplace should be ergonomically redesign to reduce frequent bending and twisting during soap baking that require inclined conveyor and handling techniques, to eliminate the identified risk factors causing WMSD among the soap baking workers.